The Distribution of Activation Markers and Selectins on Peripheral T Lymphocytes in Preeclampsia - Anna Bajnok; Maria Ivanova; János Rigó; Gergely Toldi (Hindawi Limited, 2017)
Introduction. Impaired maternal immune tolerance resulting in systemic inflammation plays a pivotal role in the pathogenesis of preeclampsia. Phenotypical changes of monocytes and neutrophil granulocytes have already been studied in preeclampsia, and some studies also included T lymphocyte activation markers; however, the results are controversial and a comprehensive analysis of activation markers is lacking. The characteristics of cellular adhesion molecules in preeclampsia are yet to be described. Material and Methods. Peripheral blood samples of 18 preeclamptic patients and 20 healthy pregnant women in the third trimester were evaluated using flow cytometry to characterize the cell surface expression of T lymphocyte activation markers and selectins. Results. We found an elevated ratio of HLA-DR and CD122-, CD62E-, and CD62L-expressing cells among the CD4+ T lymphocytes in PE in comparison to healthy pregnancy. No alterations were found in the prevalence of CD69-, CD25-, and CD62P-expressing lymphocytes and CD11c-expressing monocytes. Conclusions. Our findings support the role of activated T lymphocytes and specific cell adhesion molecules in the pathogenesis of preeclampsia.